Security administration and human rights : prospects for Nigeria's third republic and beyond - Takaya, Bala J. (Jos, Nigeria : Centre for Development Studies, University of Jos [for] the Federal Ministry of Internal Affairs, 1992)
The book is on the enforcement of constitutional human rights of citizens and safe guarding the internal and external security of the nation.
Includes bibliographical references.
ucj 16/01/2019
Loans
Keywords: Internal security -- Nigeria; Human rights -- Nigeria; Civil rights; Nigeria